Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.toxrep.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide nanoparticle synthesis (ZnO-NPs) of Knoxia sumatrensis (Retz.) DC. Aqueous leaf extract and It’s evaluation of their antioxidant, anti-proliferative and larvicidal activities

Abstract: In around the world, mosquito control is considered a most important because of the incapable of synthetic insecticides and the ecological pollution about by them. In this manner, need the eco-friendly insecticides to efficient control the mosquito disease is the need of the hour. We synthesized the eco-friendly of zinc oxide nanoparticles (ZnO-NPs) using the Knoxia sumatrensis aqueous leaf extract ( Ks- ALE) as a reducing and stabilizing agent. The synthesis of Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…The highest DPPH activity was recorded at 1000 μg/ml as 75.2% for ZnO NPs and 84.6% for L. pruinosum extract. In the present study the IC 50 of ZnO = 86.5 μg/ml, whereas Loganathan et al 15 have reported IC 50 = 95.80 μg/ml. L. pruinosum extract showed relatively higher antioxidant activity than their phyto-synthesized ZnO NPs due to the presence of secondary metabolites as confirmed by FT-IR and GC–MS results.…”
Section: Resultscontrasting
confidence: 68%
“…The highest DPPH activity was recorded at 1000 μg/ml as 75.2% for ZnO NPs and 84.6% for L. pruinosum extract. In the present study the IC 50 of ZnO = 86.5 μg/ml, whereas Loganathan et al 15 have reported IC 50 = 95.80 μg/ml. L. pruinosum extract showed relatively higher antioxidant activity than their phyto-synthesized ZnO NPs due to the presence of secondary metabolites as confirmed by FT-IR and GC–MS results.…”
Section: Resultscontrasting
confidence: 68%
“…The MCF-7 cell line was also utilized to investigate anti-breast cancer cytotoxicity, and the findings demonstrate that ZnO NPs generated from root extract of Withania somnifera had significant cytotoxicity in a dose-dependent fashion [ 167 ]. ZnO NPs biosynthesized from Knoxia sumatrensis inhibited anti-proliferative activity on MCF-7 cell line [ 168 ]. In another study, ZnO nanorods were prepared using Santalum album and dose-dependent cytotoxicity was found against MCF-7 cells.…”
Section: In Vitro and In Vivo Anticancerous Activity Of Zno Npsmentioning
confidence: 99%
“…Hydrogen peroxide solution (H 2 O 2 –FeSO 4 system) was prepared according to the method reported earlier. 30 The nanoparticle solution was mixed with an equal volume of hydrogen peroxide solution. After incubation at 37 °C for 1 h, the absorbance of the mixed solution was read at 510 nm.…”
Section: Methodsmentioning
confidence: 99%